Analisis Sistem Informasi Berbasis Cobit 5 (Studi Kasus : LTC UKSW) - NOVIAN STEVEN FARERA MESSAKH; Andeka Rocky Tanaamah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The application of IT in a company is a framework that can increase organizational profits. IT must be properly managed to generate targeted benefits. LTC is an organization that uses Cobit 5 as a tool to manage business objectives related to existing IT governance. Governance requires analysis to evaluate, assess maturity and make recommendations. LTC has not evaluated existing IT governance, so LTC does not have a framework to be able to find out the conditions, benefits and impacts of implementing IT that has been implemented. Cobit 5 is a comprehensive overall framework, because it can be adapted to existing governance in LTC. The domain on Cobit 5 the author is focused on is "Delivery, Service and Support (DSS)". This domain focuses on evaluating IT services and supporting the organization's business processes, as well as long-term control of business processes, evaluation, and planning processes. The results show that the measured processes are in DSS 1, DSS 2, DSS 3, DSS 4 and DSS 5. , DSS 6 is at level 1 (Performed Process) indicating that the process has been executed at this level and the process objectives have been achieved. Each sub-domain process is given recommendations for improvement which can later affect the current maturity level towards the level of improvement and arrive at the maturity to be achieved.